Konflik Agama di Indonesia Problem dan Solusi Pemecahannya - Firdaus M Yunus (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
The perspective of religion by placing religion as a source of conflict has led to  various attempts to reinterpret and then find common ground at a certain level with the  hope to reduce conflicts among religious communities if there is mutual tolerance. On the  exoteric level, religions are different, but on the esoteric level, religions are not similar. All  religions are viewed as equally valid paths to God. However, in many ways, the reality  shows that the tension between the religious communities is closely related to factors that  are beyond the scope of religion. This is an important matter for all religious believers to  keep the peace among them.